Diversity of medicinal plants sold in the traditional markets in Jambi, Indonesia - REVIS ASRA; MAHYA IHSAN; FITRIA ANDRIANI; MARINA SILALAHI; IZU ANDRY FIJRIDIYANTO; ANIS TATIK MARYANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Asra R, Ihsan M, Andriani F, Silalahi M, Fijridiyanto IA, Maryani AT. 2023. Diversity of medicinal plants sold in the traditional markets in Jambi, Indonesia. Biodiversitas 24: 1544-1550. Traditional markets are places for local people to do transactions of medicinal plants and traditional cooking spices. The use of plants as traditional medicine is high in Jambi Province, Indonesia. This is because the population in Jambi Province consists of several ethnicities that still practice traditional medicine. This work aims to document and inventory local knowledge of medicinal plants in Jambi's two most important markets. An interview, participatory observation, and documentation were used for data collection. There were 14 respondents of various ages chosen randomly. Data analysis used the Shannon-Wiener diversity index (H') and Jaccard similarity index (Ji). A total of 78 medicinal plant species belonging to 42 families were found. Most species were from Zingiberaceae (14 species) and Rutaceae (9 species). The diversity indexes (H') of medicinal plants at traditional markets in Jambi are high in the Angso Duo (H'= 4.295) and Talang Banjar Markets (H'= 4.277). The similarity index (Ji) in both markets was high (Ji= 88,5%). Based on the type of disease, the medicinal plants used are classified into 19 groups. The plants are mainly used for digestive disorders (29.49%), muscle tenderness (20.51%), respiratory disorders (14.10%), skin (12.82 %), and cancer (12.82 %). The part of the plant most used for medicine is fruit (26.92%), followed by rhizomes (19.23%) and flowers (15.38%). The results can be used for bioprospecting studies that will lead to the discovery of new drugs.